2023
DOI: 10.1103/physrevapplied.19.014056
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication with Non-Newtonian Fluids

Abstract: Hydrodynamic lubrication is studied for both shear thinning and viscoelastic polymer solutions. We find that elasticity, notably strong normal stresses, does not change the friction significantly for the range of parameters tested in this manuscript. Shear-thinning properties, on the other hand, do change the formation of the lubricating layer thickness and the dependence of friction on velocity relative to Newtonian fluids. A hydrodynamic model that includes shear thinning is developed and compared to experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The reduction in the thickness of a film produced by shear-thinning may mask the effects of elongational viscosity and normal stresses [21]. In fact, in a recent study on hydrodynamic lubrication with shear-thinning and viscoelastic polymer solutions, Veltkamp et al reported that the fluid's elasticity does not change friction significantly; meanwhile, shear-thinning affected the lubricant film's thickness and the dependence of friction on relative velocity in contrast to Newtonian fluids [26]. Thus, in this work, we follow a phenomenological approach to test novel viscoelastic water-based lubricants, namely, aqueous solutions of nopal mucilage, as a MWF.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in the thickness of a film produced by shear-thinning may mask the effects of elongational viscosity and normal stresses [21]. In fact, in a recent study on hydrodynamic lubrication with shear-thinning and viscoelastic polymer solutions, Veltkamp et al reported that the fluid's elasticity does not change friction significantly; meanwhile, shear-thinning affected the lubricant film's thickness and the dependence of friction on relative velocity in contrast to Newtonian fluids [26]. Thus, in this work, we follow a phenomenological approach to test novel viscoelastic water-based lubricants, namely, aqueous solutions of nopal mucilage, as a MWF.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is based on a modification of the viscous shear thinning function. Veltkamp et al, [12] developed and compared a hydrodynamic model that includes shear thinning to experimental data. The model describes the dependence on lubrication parameters well, but underestimates the lubricating layer thickness by a constant factor.…”
Section: Introductionmentioning
confidence: 99%